The Influence of the Work Environment and Work Facilities on Work Productivity Through Work Morale as an Intervening Variable at PT. Jambi Regional Development Bank Sarolangun Branch Office - Kasmir Rahim; Sigit Indrawijaya; Sri Rosita (Pusat Riset dan Inovasi Nasional, 2024)
The work provided by the company is required to be done quickly and precisely in today's increasingly advanced technological era. Changes are occurring in various fields, especially in the industrial world. Without carrying out responsive and adaptive transformation, companies risk being unable to maintain their business model and this effort is to prevent technological disruption. In this era of industrial revolution 4.0, competition in various fields cannot be avoided. All organizations, both social and economic, utilize technological advances to meet needs and be able to compete. All parties adapt to technological advances or ongoing trends so that they can survive and be able to compete. In line with the aim of surviving and being able to compete, the productivity of the organization is also expected to be effective and maximal.